Application of Zeolite-KMnO4 and Silica Gel to Extend Green Life of Manggo Arumanis (Mangifera indica L) - Anita Khairunnisa; Emmy Darmawati; Siti Mariana Widayanti (PERTETA, 2021)
Mangoes are harvested when ripe have an